1988
DOI: 10.1021/bi00411a033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of residues involved in a conformational change accompanying substitutions for glutamate-43 in staphylococcal nuclease

Abstract: A recent paper from our laboratories [Hibler, D. W., Stolowich, N. J., Reynolds, M. A., Gerlt, J. A. Wilde, J. A., & Bolton, P. H. (1987) Biochemistry 26, 6278] described the generation of site-directed substitutions for the putative general base Glu-43 in the active site of Staphylococcal nuclease (SNase) and the use of 1H NMR spectroscopy to characterize the effect of the substitutions on the conformations of the mutant proteins. The replacements for Glu-43 (Asp, Gln, Asn, Ser, and Ala) both decreased the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 13 publications
3
33
1
Order By: Relevance
“…However, in this respect, it is important to clarify a major misconception that emerged from some such studies (e.g. Hale et al 1993; Wilde et al 1998), that mutated the general base, Glu 43 , to an aspartate. Although these works found a reduction in the catalytic effect of the enzyme by a factor of 2000, which (as outlined in chapter 9 of Warshel, 1991) is fully consistent with the increase in distance to the base, it has been argued that the observed effect does not prove that Glu 43 is the base, since the mutation involves significant structural changes.…”
Section: Enzymatic Phosphoryl Transfermentioning
confidence: 99%
“…However, in this respect, it is important to clarify a major misconception that emerged from some such studies (e.g. Hale et al 1993; Wilde et al 1998), that mutated the general base, Glu 43 , to an aspartate. Although these works found a reduction in the catalytic effect of the enzyme by a factor of 2000, which (as outlined in chapter 9 of Warshel, 1991) is fully consistent with the increase in distance to the base, it has been argued that the observed effect does not prove that Glu 43 is the base, since the mutation involves significant structural changes.…”
Section: Enzymatic Phosphoryl Transfermentioning
confidence: 99%
“…However, the potential interactions between amino acid residues, with the exception of charge-charge interactions, are strongly distance-dependent (41). Also, the effects of amino acid substitutions on protein structure are often localized to the immediate vicinity of the substitution (10,(42)(43)(44)(45) used to study the effects of substitutions on other properties of the gene V protein such as resistance to irreversible thermal denaturation (31) or folding and unfolding rates (30) in the context of WT stability and DNA binding affinity. Protein engineering through the combination of singlesubstitution mutants may be most successful at adjusting those properties of concern in vitro, rather than in vivo activity.…”
mentioning
confidence: 99%
“…Tian et al (1990). a particular residue is not involved in catalysis if the kinetic properties of its mutants are not perturbed, it is difficult to unequivocally identify catalytically important residues and to quantitatively evaluate their contributions to the transitionstate stabilization unless it can be demonstrated that the structure of the mutant is not perturbed (Wilde et al, 1988).…”
mentioning
confidence: 99%